Successful treatment of G-CSF-related aortitis with prednisolone during preoperative chemotherapy for breast cancer: a case report - Yoichi Koyama; Kayo Adachi; Mio Yagi; Yoko Go; Kyoko Orimoto; Saori Kawai; Natsuki Uenaka; Miki Okazaki; Mariko Asaoka; Saeko Teraoka; Ai Ueda; Kana Miyahara; et al. (Surgical Case Reports, 2021)
Abstract Background With the introduction of dose-dense therapy, the use of primary pegfilgrastim (PEG-G) has been increasing in breast cancer treatment. A rare side effect of PEG-G is aortitis. We describe a case of PEG-G-induced aortitis. Case presentation The patient was a 43-year-old woman with stage IIA breast cancer. Due to the subtype of triple-negative breast cancer, preoperative dose-dense epirubicin–cyclophosphamide chemotherapy was started. PEG-G was administered on day 3 after the first cycle of epirubicin–cyclophosphamide chemotherapy. On day 11, she had a fever (39.4 °C) and an elevated C-reactive protein level (27.1 mg/dL). Emergency computed tomography revealed diffused wall thickening of the aortic arch without any other signs of infection. Despite administering antibiotics, her general condition and laboratory findings deteriorated until day 18. Based on these observations, she was diagnosed with PEG-G-induced aortitis. Antibiotics were discontinued, and she was treated with prednisolone thereafter. Subsequently, her clinical symptoms and laboratory findings improved around day 39. A second computed tomography scan revealed a decrease in the aortic arch wall thickening, and she was discharged on day 43. Conclusions We successfully treated PEG-G-induced aortitis using prednisolone. Although this side effect is rare, cancer patients receiving PEG-G for chemotherapy should be monitored for aortic inflammation.